Perbandingan Jenis Pola Minum Terhadap Status Hidrasi Pada Remaja Laki-Laki dan Perempuan - Grisna Febiyanti; Kunjung Ashadi (STKIP Muhammadiyah Kuningan, 2019)
Hydration status is important to maintain so that the body does not experience a lack of fluids which is referred to as dehydration and excess fluid called overhydration. If the hydration status is not considered properly the body experiences damage which has an effect on the short and long term. This study aims to compare two types of drinking patterns to hydration status, namely the planned drink and ad libitum drink. The research method used is quantitative with a descriptive approach using one shot case study design. This study used 40 research subjects consisting of 20 male students and 20 female students divided into four groups. The data analysis technique used was the test of the mean, standard deviation, and Mann-Whitney test. Based on the results of this study, there was no significant difference between the male group's planned drink and ad libitum drink. This is indicated by the results of calculations, namely the value of P> 0.05. As for the comparison of planned drink and ad libitum group of women, there were significant differences with the results of calculations that showed a P value <0.05